2002
DOI: 10.1128/mcb.22.18.6636-6647.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dyrk1A Haploinsufficiency Affects Viability and Causes Developmental Delay and Abnormal Brain Morphology in Mice

Abstract: DYRK1A is the human orthologue of the Drosophila minibrain (mnb) gene, which is involved in postembryonic neurogenesis in flies. Because of its mapping position on chromosome 21 and the neurobehavioral alterations shown by mice overexpressing this gene, involvement of DYRK1A in some of the neurological defects of Down syndrome patients has been suggested. To gain insight into its physiological role, we have generated mice deficient in Dyrk1A function by gene targeting. Dyrk1A؊/؊ null mutants presented a genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
330
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(355 citation statements)
references
References 36 publications
15
330
0
5
Order By: Relevance
“…In the mnb fly, also phenotypically similar to the human phenotype, efficient synaptic vesicle recycling is promoted. 7,9,34 Retino-cortical visual processing defects and body and wing size reduction are seen in both Dyrk1a ( ± ) and the mnb fly. 35,36 Dyrk1a-haploinsufficient mice show severe glucose intolerance and decreased beta cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mnb fly, also phenotypically similar to the human phenotype, efficient synaptic vesicle recycling is promoted. 7,9,34 Retino-cortical visual processing defects and body and wing size reduction are seen in both Dyrk1a ( ± ) and the mnb fly. 35,36 Dyrk1a-haploinsufficient mice show severe glucose intolerance and decreased beta cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Furthermore, data from both animal models and humans have suggested that decreased DYRK1A expression is also pathogenic. [7][8][9] Pathogenic variants in DYRK1A resulting in haploinsufficiency of the gene have recently been proposed to cause intellectual disability (ID), mental retardation autosomal dominant type 7 (MIM 614104) in individuals with translocations, 10 single-nucleotide variants (SNVs), 11,12 and intragenic microdeletions 11,[13][14][15][16][17] disrupting only DYRK1A.…”
Section: Introductionmentioning
confidence: 99%
“…The DYRK1A gene, which is carried on YAC152F7 but not on YAC141G6, encodes a serine threonine kinase. A study of mice with only one active copy of DYRK1A (heterozygous for DYRK1A invalidation) showed that a decrease in DYRK1A expression decreases the size of the ventral regions of the brain, including the thalamus-hypothalamus area (Fotaki et al, 2002). This finding suggests that, in YAC152F7 transgenic mice, which carry three copies of DYRK1A, DYRK1A overexpression is responsible for phenotypic changes opposite to those observed in heterozygous mice with one copy of DYRK1A.…”
Section: Discussionmentioning
confidence: 99%
“…DYRK1A has been considered a good candidate gene for the Down syndrome phenotypic abnormalities (reviewed in Epstein, 2000;Vicari et al, 2000;Nadel, 2003) due to its localization in the Down syndrome critical region of chromosome 21 (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), its overexpression in the brain of Down syndrome patients (Guimera et al, 1999), and the neurobehavioral alterations shown by transgenic mice overexpressing the gene (Smith and Rubin, 1997;Altafaj et al, 2001). The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002). Moreover, brains of patients with Down syndrome present size reduction, increased astrocyte number, delayed myelination, and several abnormal neuronal differentiation processes (reviewed in Coyle et al, 1986;Becker et al, 1991;Raz et al, 1995).…”
Section: Discussionmentioning
confidence: 99%